2022
DOI: 10.1002/cpt.2558
|View full text |Cite
|
Sign up to set email alerts
|

Drug Disposition Protein Quantification in Matched Human Jejunum and Liver From Donors With Obesity

Abstract: Mathematical models, such as physiologically‐based pharmacokinetic models, are used to predict, for example, drug disposition and toxicity. However, populations differ in the abundance of proteins involved in these processes. To improve the building and refinement of such models, they must take into account these interindividual variabilities. In this study, we used global proteomics to characterize the protein composition of jejunum and liver from 37 donors with obesity enrolled in the COCKTAIL study. Liver p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 62 publications
1
34
0
Order By: Relevance
“…The protein quantification has been described previously. 30 In brief, proteins were extracted from liver and jejunal biopsies in a sodium dodecyl sulfate (SDS)containing (2% w/v) lysis buffer, and processed with the multi-enzyme digestion filter-aided sample preparation protocol, using LysC and trypsin. Proteomics analysis was performed with Q Exactive HF or Q Exactive HF-X.…”
Section: Protein Quantification Of Cyp Enzymes In Liver and Jejunal B...mentioning
confidence: 99%
“…The protein quantification has been described previously. 30 In brief, proteins were extracted from liver and jejunal biopsies in a sodium dodecyl sulfate (SDS)containing (2% w/v) lysis buffer, and processed with the multi-enzyme digestion filter-aided sample preparation protocol, using LysC and trypsin. Proteomics analysis was performed with Q Exactive HF or Q Exactive HF-X.…”
Section: Protein Quantification Of Cyp Enzymes In Liver and Jejunal B...mentioning
confidence: 99%
“…The estimated thiamine portal vein concentration of ~ 0.5 μM is close to saturating ThTR‐2 and suggests that both OCT1 and ThTR‐2 could play a role in hepatic uptake of thiamine. OCT1 expression levels in the liver are much higher than ThTR‐2 levels, 41 consistent with it being a higher capacity thiamine transporter; thus, OCT1 may increasingly play a more predominant role in hepatic thiamine uptake at increasing oral thiamine doses. Our results are not consistent with the results of a study investigating the disposition of a high dose (200 mg) of thiamine in individuals with reduced function OCT1 polymorphisms, which showed no effect of the polymorphisms on thiamine disposition at this dose 40 .…”
Section: Discussionmentioning
confidence: 83%
“…Wegler et al reported the protein levels of drug-metabolizing enzymes and transporters in the jejunum using a large sample size. 53 Direct comparison of our data with theirs is difficult because the MSbased DIA untargeted proteomics used in our study are generally considered not applicable for comparisons of expression levels among different proteins. However, the present results together with the report of Wegler et al would be useful for elucidating interindividual and regional differences in the expressions of pharmacokinetics-related proteins in the human intestine.…”
Section: ■ Discussionmentioning
confidence: 99%
“…One of the limitations in this study is that the sample sizes were relatively small (61 biopsy samples, 61 samples for RNA-seq, and 27 samples for LC–MS/MS); the numbers of biopsies of the jejunum and rectum were particularly at 3 each. Wegler et al reported the protein levels of drug-metabolizing enzymes and transporters in the jejunum using a large sample size . Direct comparison of our data with theirs is difficult because the MS-based DIA untargeted proteomics used in our study are generally considered not applicable for comparisons of expression levels among different proteins.…”
Section: Discussionmentioning
confidence: 99%